PENGARUH PRODUCT QUALITY, PRICE PERCEPTION, BRAND TRUST, DAN ELECTRONIC WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN PRODUK SKINCARE GLAD TO GLOW PADA APLIKASI SHOPEE DI SURABAYA - Dewi Aulia Rismala; Istiono (STAI Denpasar Bali, 2026)
This study aims to analyze and prove the influence of Product Quality, Price Perception, Brand Trust, and Informal Communication between Consumers that takes place through Digital Media on Purchase Decisions for Glad to Glow skincare products among Shopee application users in Surabaya. This study uses a quantitative method by distributing questionnaires to respondents who meet the research criteria. Data analysis techniques used include Descriptive Tests, Instrument Tests, Classical Assumption Tests, and Hypothesis Tests through Multiple Linear Regression with the help of SPSS 26. This study was conducted in 2025. The results of the study indicate that all indicators in the research instrument are declared valid and reliable. Based on the Multiple Linear Regression Test, the variables of Price Perception and Informal Communication between Consumers that take place through Digital Media have a more dominant influence on Purchase Decisions, while Brand Trust shows the lowest and insignificant influence. The results of the T Test show that Product Quality, Price Perception, and Informal Communication between Consumers that take place through Digital Media have a significant influence on Purchase Decisions, while Brand Trust has no significant influence. The F Test confirms that simultaneously the four independent variables have a significant influence on Purchase Decisions. The results of the Coefficient of Determination (R²) test indicate that the independent variables are able to explain most of the variation in Purchase Decisions, while the remainder is influenced by other variables outside the study.